Effect of calcium and magnesium in identification of baby in highsugar mammals - Chandraju, S.; Beirami, Ashraf; Kumar, C. S. Chidan (Research in Biotechnology, 2011)
Effects of calcium and magnesium in diet to determine baby gender in high-sugar mammals have been investigated. Diabetes mellitus is a chronic, widely spread disease in living species. Sex determination has scientific basis for prevention of genetic diseases in addition to social backgrounds.60 rats (obtained from veterinary college Bangalore), were divided in to three groups in the ratio male to female 1:5. The first group was made diabetic with Ca and Mg, the second group was non diabetic with Ca and Mg, group third was control unit (Non-diabetic without Ca and Mg). It was found that the delivered offspring male to female ratios were 4:1, 3.77:1 and 1.05:1 for the first, second and third groups respectively. Also, it was found that non diabetic rats fed with normal food yields maximum numbers of offspring (220), while non diabetic rat fed with Ca and Mg yields 205 and diabetic rats with Ca and Mg yield lowest numbers of offspring (130).